2017
DOI: 10.1038/nplants.2017.18
|View full text |Cite|
|
Sign up to set email alerts
|

A CRISPR–Cpf1 system for efficient genome editing and transcriptional repression in plants

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)-Cpf1 has emerged as an effective genome editing tool in animals. Here we compare the activity of Cpf1 from Acidaminococcus sp. BV3L6 (As) and Lachnospiraceae bacterium ND2006 (Lb) in plants, using a dual RNA polymerase II promoter expression system. LbCpf1 generated biallelic mutations at nearly 100% efficiency at four independent sites in rice T0 transgenic plants. Moreover, we repurposed AsCpf1 and LbCpf1 for efficient transcriptional repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
410
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 487 publications
(446 citation statements)
references
References 16 publications
15
410
3
1
Order By: Relevance
“…Cpf1 from Acidaminococcus sp. (AsCpf1) and Lachnospiraceae bacterium (LbCpf1) have been shown to be functional in rice, soybean and tobacco [34,[56][57][58]. In these plants, LbCpf1 mutagenesis efficiency, which seems to be correlated with the target sequence [56], appeared always higher than those of AsCpf1, reaching sometimes 100% in rice [58].…”
Section: Cas-like Proteinsmentioning
confidence: 99%
“…Cpf1 from Acidaminococcus sp. (AsCpf1) and Lachnospiraceae bacterium (LbCpf1) have been shown to be functional in rice, soybean and tobacco [34,[56][57][58]. In these plants, LbCpf1 mutagenesis efficiency, which seems to be correlated with the target sequence [56], appeared always higher than those of AsCpf1, reaching sometimes 100% in rice [58].…”
Section: Cas-like Proteinsmentioning
confidence: 99%
“…Spacer sequences were inserted into the crRNA that guides Cpf1 to the target by annealing a phosphorylated oligonucleotide dimer into a Type IIS cloning site before assembly into the final plasmid (Figure 2A). In contrast, Tang et al [39] flanked the crRNA with self-cleaving ribozymes enabling them to drive expression in rice from a strong constitutive promoter ( Figure 2B). Notably, Tang et al [39] reported 100% mutation efficiency, with very few plants being genetic chimeras.…”
Section: Toolkits For Targeted Mutagenesismentioning
confidence: 99%
“…In contrast, Tang et al [39] flanked the crRNA with self-cleaving ribozymes enabling them to drive expression in rice from a strong constitutive promoter ( Figure 2B). Notably, Tang et al [39] reported 100% mutation efficiency, with very few plants being genetic chimeras.…”
Section: Toolkits For Targeted Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major findings is that the choice of promoters for expressing Cas9 has a dramatic impact on the efficiency and heritability of gene editing in Arabidopsis . Another effort has been to isolate and characterize additional nucleases such as Cpf1 that have characteristically different PAM requirements and that generate DSBs with cohesive ends (Tang et al, 2017). …”
mentioning
confidence: 99%